Taxonomic structure of the algal flora of Iran (Bangladesh Journal of Plant Taxonomy, 2009)
Algal floristic work carried out in Iran between 1853 and 1981 have been reviewed and compared with the results obtained in a series of recent studies (2000-2007). Algal samples for the recent studies were collected mainly from different inland aquatic habitats. On the basis of data from published and the recent studies, the systematic list of algae shows the occurrence of 1304 species and 1559 infra-specific taxa in Iran. However, 1213 species (1443 infra-specific taxa) revealed from the recent studies included 812 species (979 infra-specific taxa) as new reports for Iran (63% of the total species recorded). Analysis on taxonomic structure of algal flora of Iran testifies its richness. The basic parameters of a regular diversification of flora, values of genera quotient, spectra of leading taxa confirm that the highest percentage is contributed by Bacillariophyta (43%) of the total number of specific and infra-specific taxa followed by Chlorophyta (25%), Cyanophyta (15%) and Euglenophyta (8%). On an interrelation among divisions of algae, the algal flora of Iran appeared to be closer to that of Turkmenistan. Keywords: Algal flora; Taxonomic quotient; Water body; Iran. DOI: 10.3329/bjpt.v16i2.3933 Bangladesh J. Plant Taxon. 16(2): 185-194, 2009 (December)